Diet Supplementation with NUTRIOSE, a Resistant Dextrin, Increases the Abundance of Parabacteroides distasonis in the Human Gut. Issue 11 (4th April 2022) - Thirion, Florence; Da Silva, Kévin; Plaza Oñate, Florian; Alvarez, Anne‐Sophie; Thabuis, Clémentine; Pons, Nicolas; Berland, Magali; Le Chatelier, Emmanuelle; Galleron, Nathalie; Levenez, Florence; Vergara, Coralie; Chevallier, Hélène; et al.
Abstract : Scope: An imbalance of the gut microbiota ("dysbiosis") is associated with numerous chronic diseases, and its modulation is a promising novel therapeutic approach. Dietary supplementation with soluble fiber is one of several proposed modulation strategies. This study aims at confirming the impact of the resistant dextrin NUTRIOSE (RD), a soluble fiber with demonstrated beneficial health effects, on the gut microbiota of healthy individuals. Methods and results: Fifty healthy women are enrolled and supplemented daily with either RD ( n = 24) or a control product ( n = 26) during 6 weeks. Characterization of the fecal metagenome with shotgun sequencing reveals that RD intake dramatically increases the abundance of the commensal bacterium Parabacteroides distasonis . Furthermore, presence in metagenomes of accessory genes from P. distasonis, coding for susCD (a starch‐binding membrane protein complex) is associated with a greater increase of the species. This suggests that response to RD might be strain‐dependent. Conclusion: Supplementation with RD can be used to specifically increase P. distasonis in gut microbiota of healthy women. The magnitude of the response may be associated with fiber‐metabolizing capabilities of strains carried by subjects. Further research will seek to confirm that P. distasonis directly modulates the clinical effects observed in other studies. Abstract : Dietary supplement with the resistant dextrin NUTRIOSE, a soluble fiber, increases the abundance of Parabacteroides distasonis in the gut microbiota of healthy women. Magnitude of P. distasonis increase is related to the presence of a pair of genes annotated as susCD, a starch‐binding membrane protein complex, in the specific strains carried by individuals.